IMPLEMENTATION OF LEARNING MODELS IN THE MERDEKA CURRICULUM: PERCEPTION OF VOCATIONAL HIGH SCHOOL ACCOUNTING TEACHERS IN THE SPECIAL REGION OF YOGYAKARTA - Purnama, Dian Normalitasari; Siswanto, Siswanto; Aghni, Rizqi Ilyasa; Astuti, Vera (Jurnal Ekonomi dan Pendidikan, 2024)
Education plays a crucial role in shaping the quality of human resources and societal development. Effective learning processes, significantly influenced by teacher performance, are vital for achieving quality education. This research explores the challenges faced by vocational high school teachers in implementing the Merdeka Curriculum, which aims to address learning disruptions caused by the Covid-19 pandemic and align with the demands of Industry 4.0. The study employs a qualitative case study design involving interviews and observations of 10 accounting teachers from five vocational high schools in Yogyakarta. Findings reveal that while various learning models, including Problem Based Learning (PBL), Project Based Learning (PjBL), and Teaching Factory (TEFA), are utilized, their implementation is often hindered by limited teacher training, inadequate resources, and insufficient understanding of the curriculum. PBL faces difficulties in Vocational High School A and Vocational High School D due to a lack of training. PjBL is effectively used in Vocational High School C and Vocational High School D for real-world projects, whereas TEFA is constrained by limited support. The study highlights that teachers struggle with adapting to the Merdeka Curriculum, particularly senior educators, and emphasizes the need for professional development, improved infrastructure, and additional training to meet the curriculum's requirements. Key barriers include inadequate professional support, high administrative burdens, and resistance to change. This research underscores the importance of enhancing teacher readiness and adapting learning models to align with the Merdeka Curriculum effectively.